Pertumbuhan Siput Lola (Trochus niloticus L. 1767) di Perairan Kepulauan Banda Naira Kabupaten Maluku Tengah - Abukena, Safrudin La; Wardiatno, Yusli; Setyobudiandi, Isdradjat; Khouw, Abraham S (JURNAL BIOLOGI INDONESIA, 2014)
Maluku as a major producer, reached the highest production of siput lola (T. niloticus) in 1989 with production about 250tons (6.8 billion) but then drastically decreased to 14.2 tons in 2005. This study was conducted over 16 months (March2012 - June 2013) in the waters of the Banda Islands. The purpose of the study was to determine the individual andpopulation growth of trochus snails. Individual growth rate (K) of siput lola resource for deameter basalt (DB) was equal to0.2439 (von Bertalanffy models) and 0.3571 (Gompertz models). Maximum size (S?) that could be achieved for deameterbasalt was equal to 91.73 mm (von Bertalanffy models) and 88.52 mm (Gompertz models). The population growth rate(r) of siput lola resource was at 0.1469 with a maximum amount that could be reached as many as 401 ind or 122ind ha-1 (von Bertalanffy models) and 191 ind or 58 ind ha-1 (Gompertz models) within a period of 24 months.Keywords : Growth, Trochus niloticus, Banda Naira islands